Undertaking Family-Focused Interventions When a Parent Has a Mental Illness - Possibilities and Challenges. Issue 2 (8th April 2021) - Yates, Scott; Gatsou, Lina
Abstract : Parental mental illness (PMI) is a public health issue associated with risks of negative outcomes for children and families. Effective whole family interventions with families with PMI are still not well implemented across mental health, social work and multi-agency workforces. This paper presents research with professionals trained in a new programme, the Think Family-Whole Family Programme, to strengthen family-focused work around PMI. It examines professionals' practice and understanding of PMI and identifies enablers of effective practice. Findings indicate that professionals having appropriate knowledge of how PMI can affect families and the confidence to address it are important factors enabling effective work with them. They also had concerns around how to discuss mental health due to issues of stigma and management support of whole-family work. Results indicate potential for training to achieve positive outcomes in improving professionals' knowledge and confidence and encouraging whole-family work around PMI. Possibilities and challenges for future work with families with PMI are discussed.